System-in-use methodology : a methodology to generate conceptual PSS (Product-Service Systems) and conventional designs using systems-in-use data - Hussain, Romana (Cranfield University, 2013)
Industries want to add value to their offerings but to do this, rather than just accepting customer requirements, they now need to know how their products and/or services have been embedded within their customer’s process to achieve a goal that the customer has; any gaps within the process then present an opportunity for the provider to fill these gaps. The System-In-Use (SIU) Methodology presented in this thesis facilitates customer issues in “pulling” the supply chain into creating new solutions as well as the supply chain “pushing” new value propositions into improving customer processes. It does this by drawing on a detailed theory of value and capability which was developed as part of this research. The method has been applied in five industries in processes encompassing high value-assets with very positive outcomes for each of the stakeholders involved: notably, three solutions have been adopted in industry for which a KT-Box award was granted by Cambridge University. Cont/d.
Keywords: PSS Conceptual Design; Closed Loop Design; Business Model Innovation